The NIH Science of Behavior Change Program: Transforming the science through a focus on mechanisms of change. (February 2018) - Nielsen, Lisbeth; Riddle, Melissa; King, Jonathan W.; ,; Aklin, Will M.; Chen, Wen; Clark, David; Collier, Elaine; Czajkowski, Susan; Esposito, Layla; Ferrer, Rebecca; Green, Paige; et al.
Abstract: The goal of the NIH Science of Behavior Change (SOBC) Common Fund Program is to provide the basis for an experimental medicine approach to behavior change that focuses on identifying and measuring the mechanisms that underlie behavioral patterns we are trying to change. This paper frames the development of the program within a discussion of the substantial disease burden in the U.S. attributable to behavioral factors, and details our strategies for breaking down the disease- and condition-focused silos in the behavior change field to accelerate discovery and translation. These principles serve as the foundation for our vision for a unified science of behavior change at the NIH and in the broader research community. Highlights: Poor health behaviors account for a substantial proportion of disease burden in the U.S. Behavior change is powerful at addressing this challenge, but it is difficult to get people to initiate and sustain desired behavioral change. Scientific silos and a lack of focus on mechanisms of change have hindered progress in the behavior change field. Precisely identifying mechanistic targets and adopting the experimental medicine approach can unify and advance the field.